Gaucher Disease: An Unusual Cause of Knee Pain. (11th October 2022) - Gigis, Ioannis; Pitsilos, Charalampos; Samoladas, Efthimios; Pavlopoulos, Charalampos; Hytiroglou, Prodromos; Ditsios, Konstantinos; Papadopoulos, Pericles
Abstract : Introduction: Gaucher disease (GD) is a genetic lysosomal disorder leading to storage of the glycolipid molecule glucocerebroside in macrophages, causing multiorgan dysfunction. Bone marrow involvement may result in painful bone crisis and hematologic disturbance. Case Report: We present a case of a 13-year-old adolescent boy with right knee pain. Radiograph and magnetic resonance imaging of the distal femur indicated possible osteomyelitis or bone tumor. However, histologic examination of bone biopsy material suggested the diagnosis of GD, which was confirmed by detection of decreased β-glucocerebrosidase activity and identification of the exact gene mutation. Discussion: Many visceral and bone abnormalities of GD have been described. The diagnosis of GD is based on clinical and laboratory findings and is established by the measurement of β-glucocerebrosidase dysfunction and the study of GBA gene mutations. Treatment is currently based on enzyme replacement and substrate reduction. Conclusion: This is a rare case of GD presenting initially with knee pain. Because early diagnosis is important for the treatment of this condition, orthopaedic surgeons should consider this uncommon cause in the differential diagnosis of joint pain.